Lesbian, Gay, Biseksual dan Trans/ender Ditinjau darl Agama Islam - Miftakhul Anwar (JURNAL KAJIAN ISLAM MODERN, 2020)
LGBT (Lesbian, Gay, bisexual and transgender) issues always arise without a clear resolution. In Islamic theology, GBT behavior is behavior that is prohibited by Allah SWT and His Messenger, including in the teachings of other religions, is behavior that is disapproved and that must be shunned. LGBT behavior is a heinous behavior that is hated by Allah SWT so that in the history of human civilization Allah punished the perpetrators by being showered with stones from hell until they were left with none, and the Prophet Muhammad SAW also criticized the perpetrators by threatening them with severe punishment. The scholars from the time of the Companions to the 20th century also agreed/consented that LGBT behavior is a heinous act that is unlawful, and there is no difference of opinion among the scholars. The only difference is in punishing LGBT perpetrators, that is, there are those who are absolutely killed (malikiyyah and hanabalah schools) and there are those who are punished like adulterers (syafi'i madzhab) and there are those who think that the punishment is ta'zir according to the judge's considerations (hanafiyyah madzhab opinion).